Resultatmåling i nyt terræn. En undersøgelse af måleusikkerheder på det specialiserede ungeområde - Mikkelsen, Britt Søvsø; Nielsen, Jeppe Agger (Politik, 2014)
The idea of measuring results and e ects has gained prevalence in an increasing number of policy areas. e specialised youth area represents one of the „soft“ service areas in which Danish municipalities increas- ingly have introduced performance measurement systems. However, research regarding the bene ts of these systems is scarce. is article therefore examines the challenges of measuring e ects of municipal initiatives in the specialised youth area based on a case study of Aarhus Municipality’s use of result documentation. We demonstrate how result documentation is subject to considerable uncertainty. Accurate measurements are complicated by the character of the area and by the fact that the municipality’s initiatives take place in a context where many simultaneous changes occur.